Psychosocial Stimulation Interventions to Optimise The Developmental Growth Process of Stunted Toodlers in The First 1000 Days of Life: A Systematic Review - Azwar, Azwar; Setiawan, Agus; Rahmadiyah, Dwi Cahya (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This systematic review investigates the efficacy of psychosocial stimulation interventions in improving the developmental outcomes of stunted toddlers during their first 1000 days of life. We used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to analyse 13 articles that met strict inclusion criteria from various scientific disciplines. Our findings reveal that interventions emphasising family empowerment, enhanced hygiene, and strategic health education significantly impact child growth and cognitive development. Community-based approaches, including cash transfers and educational programs, support sustainable development in resource-limited settings. This review also identifies the importance of cultural adaptation in intervention strategies, ensuring community acceptance and effective implementation. Despite the promising outcomes, the variability in research methodologies and the focus on specific socio-economic contexts limit the generalizability of the results. Future research should expand the studies' geographical and cultural scope to validate these findings comprehensively. The implications of this review support the integration of psychosocial stimulation into public health policies, highlighting its potential to improve developmental trajectories and reduce stunting in affected populations substantially.